2015
DOI: 10.1186/s12917-015-0410-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary organic acids and botanicals on intestinal integrity and inflammation in weaned pigs

Abstract: BackgroundOrganic acids, such as citric and sorbic acid, and pure plant-derived constituents, like monoterpens and aldehydes, have a long history of use in pig feeding as alternatives to antibiotic growth promoters. However, their effects on the intestinal barrier function and inflammation have never been investigated. Therefore, aim of this study was to assess the impact of a microencapsulated mixture of citric acid and sorbic acid (OA) and pure botanicals, namely thymol and vanillin, (PB) on the intestinal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 34 publications
3
53
0
Order By: Relevance
“…Beside the promising application of organic acids and botanicals for foodborne pathogens control, selected combinations of organic acids such as citric and sorbic acid together with monoterpenes were shown to exert a direct effect on the intestinal mucosa, by improving the barrier integrity of Caco-2 intestinal cells, without the mediation of the microflora. When these active ingredients were encapsulated in a lipid matrix and fed to weaning pigs, improved barrier functionality in jejunum and ileum and reduced local and systemic inflammatory pressure were observed and then translated in better growth performance [125].…”
Section: Use Of Protected Vs Free Organic Acidsmentioning
confidence: 99%
“…Beside the promising application of organic acids and botanicals for foodborne pathogens control, selected combinations of organic acids such as citric and sorbic acid together with monoterpenes were shown to exert a direct effect on the intestinal mucosa, by improving the barrier integrity of Caco-2 intestinal cells, without the mediation of the microflora. When these active ingredients were encapsulated in a lipid matrix and fed to weaning pigs, improved barrier functionality in jejunum and ileum and reduced local and systemic inflammatory pressure were observed and then translated in better growth performance [125].…”
Section: Use Of Protected Vs Free Organic Acidsmentioning
confidence: 99%
“…Drip loss at 72 h and cooking loss were also unaffected by dietary treatments. Gheisar et al [28] reported a linear decrease in drip loss across increasing levels of the same supplement after 5 days and up to 7 days of storage. Overall, in the present study, after 72 h of refrigerated storage, drip loss was lower than those reported (around 9.4%) by the latter authors.…”
Section: Discussionmentioning
confidence: 98%
“…Few studies have focused on the use of a blend of OA and EO in poultry, and results are often controversial compared to medicated dietary treatments [28,29]. Microencapsulation of a blend of the two groups of additives avoids the action of the stomach allowing the slow release of compounds at gut level, thus improving the additives' antibacterial action beyond the enhancement of growth performance [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations